2011
DOI: 10.1182/blood-2011-07-367904
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Escherichia coli asparaginase antibody levels determine the activity of second-line treatment with pegylated E coli asparaginase: a retrospective analysis within the ALL-BFM trials

Abstract: Hypersensitivity reactions limit the use of the antileukemic enzyme asparaginase (ASE). We evaluated Ab levels against Escherichia coli ASE and ASE activity in 1221 serum samples from 329 patients with acute lymphoblastic leukemia who had received ASE treatment according to the ALL-BFM 2000 or the ALL-REZ BFM 2002 protocol for primary or relapsed disease. ASE activity during first-line treatment with native E coli ASE and second-line treatment with pegylated E coli ASE was inversely related to anti-E coli ASE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 26 publications
(35 reference statements)
1
59
0
2
Order By: Relevance
“…Sixth, our study shows that the presence of AAAs is related to allergy to and silent inactivation of asparaginase as shown by others, 10,20 but predicting asparaginase allergy or silent inactivation based on antibody formation is hampered by low specificity (64%) of the test. The specificity of the Coli-AAA test in intensification was higher, 73%, but still not perfect.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Sixth, our study shows that the presence of AAAs is related to allergy to and silent inactivation of asparaginase as shown by others, 10,20 but predicting asparaginase allergy or silent inactivation based on antibody formation is hampered by low specificity (64%) of the test. The specificity of the Coli-AAA test in intensification was higher, 73%, but still not perfect.…”
Section: Discussionsupporting
confidence: 56%
“…In the PEGasparaginase study, the PEGasparaginase activity trough levels and AAAs were measured in serum at the start of intensification (week 0); in weeks 2,4,6,8,10,14,16,24,26, and 28; and also 1 week after administration in weeks 3, 9, 15, and 25. Serum asparagine, aspartic acid, glutamine, and glutamic acid levels were measured at weeks 0, 2, 4, 14, and 24 during PEGasparaginase therapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…201,202 Moreover, a recent study showed that high anti-asparaginase antibody level after initial therapy with native E coli asparaginase was associated with decreased asparaginase activity during subsequent therapy with PEG-asparaginase. 203 In contrast, no cross-reactivity between antibodies against native E coli asparaginase and Erwinia asparaginase was reported, 201,202 and enzyme activity of Erwinia asparaginase was not affected by the presence of anti-E coli asparaginase antibodies. 203 A study from the DFCI ALL Consortium showed the feasibility and activity of using Erwinia asparaginase in pediatric and adolescent patients who developed hypersensitivity reactions to E coli asparaginase during frontline therapy; importantly, treatment with Erwinia asparaginase did not negatively impact EFS outcomes in these patients.…”
Section: Nccn Recommendations For Supportive Carementioning
confidence: 91%
“…203 In contrast, no cross-reactivity between antibodies against native E coli asparaginase and Erwinia asparaginase was reported, 201,202 and enzyme activity of Erwinia asparaginase was not affected by the presence of anti-E coli asparaginase antibodies. 203 A study from the DFCI ALL Consortium showed the feasibility and activity of using Erwinia asparaginase in pediatric and adolescent patients who developed hypersensitivity reactions to E coli asparaginase during frontline therapy; importantly, treatment with Erwinia asparaginase did not negatively impact EFS outcomes in these patients. 204 Thus, for patients who develop severe hypersensitivity reactions during treatment with E coli asparaginase (either to the native or pegylated formulation), the use of E coli-derived formulations should be stopped and Erwinia asparaginase should be substituted (see "Sup-portive Care: Asparaginase Toxicity Management" on page 868).…”
Section: Nccn Recommendations For Supportive Carementioning
confidence: 91%